Manpower and Employees’ Attitudes Are Very Important in An Organisation - Chang Jin Kiat; Daisy Mui Hung Kee; Aiy Siew A/P Ah Chai; Ghalia Jamal; Soo Mei Chen; Tiong Zih Lin (International Journal of Applied Business and International Management, 2019)
KFC or also known as Kentucky Fried Chicken is one of the most leading fast food restaurants around the world. KFC that originally from America has thrived around the world including Malaysia and Kuwait. Although it is an advanced company, it still has some sensitive internal issues that will cause problems to the company. If this problem is not carefully and wisely deal with, it will drop the company name and bring a negative impact to everyone that involved in the company. In this research, we examine the issues in an organization and KFC is the subject of our study. KFC has been in a bad mood for the past few years. Many of the customers complaint about the services and the attitudes of the employee in the restaurant. In Jan 2015, a case of brawl between KFC employees and customers was viral in social media and there also a case where KFC employees show pornographic signs to customers. This shows the attitude and the behavior of KFC employees who do not adhere to ethics and are not prudent will affect the good name of a company. Employees issues in KFC is the best topic to be discuss in this study. There lot of problem that face by KFC in term of employees such as lack of manpower in their branches. If compare from our observation, there a huge difference between the number of workers in KFC and its competitor, Mc Donald. Therefore, we can see that Mc Donald is more efficient than KFC although KFC has lower cost for their human resource.